Pengaruh Akuntabilitas, Transparansi dan Partisipasi Masyarakat terhadap Pengelolaan Dana Desa se- Kecamatan Sambi Boyolali - Nita Maina; Johny Subarkah; Yuwita Ariessa Pravasanti (Nur Science Institute, 2022)
This study aims to determine the effect of accountability, transparency, and community participation and village fund management empirical studies at Village Offices throughout Sambi District, Boyolali Regency. This type of quantitative research using primary data by distributing questionnaires to respondents. The population in this study were village officials and village consultative bodies in 16 Village Offices. The sample selection method was purposive sampling so as to get 64 respondents consisting of the Village Head, Village Secretary, and Village Treasurer and the head of the Village Consultative Body. Based on the results of the t-test that has been carried out, it can be seen that accountability partially affects the management of village funds and transparency and community participation have no effect on the management of village funds. However, based on the F test, it is known that accountability, transparency and community participation have a simultaneous effect on the management of village funds.